Communities: development of church-based counselling teams - Potgieter, Stella D. (AOSIS, 2015)
Pastoral care is a biblical mandate to the Church to be involved in the lives of God's people. A key metaphor used by Jesus to describe his pastoral role was that of a shepherd. Thus, to be God's shepherds and instruments of healing and transformation in God's world is an imperative to all people, clergy and laity alike. The brokenness in South African society is strikingly apparent, exacerbated by the effects of exceptionally high criminal behaviour as statistics show. The demand for pastoral care and assistance with various personal problems is on the increase, with many non-church goers turning to churches for help. Also apparent in South Africa is the acute shortage of trained individuals to offer care and counselling. The task of offering care is not the sole responsibility of clergy, as all are called to be shepherds and caregivers. The importance and urgency in training church-based counselling teams cannot be overstated. More so in that we are becoming increasingly aware that not only are individuals in need of care, but whole communities are struggling with trauma and life's challenges, and often do not know whom to turn to. In pursuance of the realisation that pastoral care is the function and duty of all Christians, this article will delineate in particular an explanation of lay counselling, reasons for its importance including biblical foundations, where and how ordinary South Africans can get involved, and will propose certain models and approaches for getting started. These models will not be discussed in depth, but present an opportunity for the next. Teams for these models consist of professional counsellors, but ought not to be restricted to a select few, as all are called to this special ministry and can be trained for the task, which will include on-going supervision and mentoring. The overall purpose of this article is to highlight the urgency of training lay counsellors and some recommendations will be made how to apply it, in an attempt to be faithful to the biblical mandate and examples set by Jesus Christ.
Keywords: Ordinary counsellors; laity; pastoral counselling; pastoral care